TYPES OF KNOWLEDGE IN THE TEACHING OF BAHAUDDIN NAQSHBAND - Gulchehra Navruzova Negmatovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
Philosophical analysis of the notions of ​​the founder of the Naqshbandiya teaching Bahauddin Nakshband about knowledge is presented in the state. It is proven that he was glorified as "Namaki mashoih" on the basis of "Risolai unsia" by Yaqubi Charxiy. The description of two types of science is substantiated: the science of the heart and the science of language, a comparative analysis of science and the science of nature, the science of the future and education about the future.